Structure, mechanical and tribological properties of Ti-doped and Cr-doped a-C:H:SiOx coatings; Vacuum; Vol. 219, Pt. A - Grenaderov A. S. Aleksandr Sergeevich; Solovjev A. A. Andrey Aleksandrovich; Oskirko V. O. Vladimir Olegovich; Oskomov K. V. Konstantin Vladimirovich; Semenov V. A. Vyacheslav Arkadjevich; Sypchenko V. S. Vladimir Sergeevich; Saraev A. A. Andrey Aleksandrovich (2024, 2024)
Title screen